Catatan Masa Lalu Terkait Pencapresan Prabowo dan Prediksi Indonesia di Masa Depan - Sopian , Sopian (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Jokowi's role and involvement in supporting Prabowo began before the Prabowo-Gibran pair's nomination in the 2024 presidential election. Allegations of presidential campaign violations were also directed at Jokowi when he showed his support for the pair, likewise with Jokowi's other actions that are full of interest. This descriptive qualitative approach using literature studies analyzes texts from several literature including news from online news portals. The texts are interpreted in such a way through data analysis techniques according to the research questions. The results of the analysis/research include: (1) there is a counter-narrative to Jokowi's role or influence during Prabowo's leadership as president; between Jokowi's continued influence and his diminishing influence; (2) predictions of Indonesia's leadership during Prabowo's leadership have the potential to be authoritarian or democratic; (3) predictions regarding the Indonesian economy during Prabowo's era, namely between being difficult to improve and Prabowo's optimism. Prabowo, Jokowi, and Gibran are the main political actors in the narrative that is built. The texts reflect the complex dynamics of political communication between the three main figures. However, political communicators from various circles are quoted in news texts.